Analisis Hukum tentang Hak Pekerja atas Perjanjian Kerja Waktu Tertentu (PKWT) yang tidak ditandatangani oleh PT Mega Central Finance (Studi Putusan Pengadilan Negeri Jakarta Pusat Nomor 216/Pdt.Sus-PHI/2025/PN Jkt.Pst) - Dela Veliza; Dessya Indira Bunga Kristika; Keisya Aulia Hakiki; Nurul Naila Amelia; Rahmatul Hasanah; Sesilia S; Luthy Yustika (Media Hukum Indonesia (MHI), 2026)
This research explores the legal protection of workers under an unsigned Fixed-Term Employment Agreement (PKWT) through the Industrial Relations Court Decision No. 216/Pdt.Sus-PHI/2025/PN Jkt.Pst.  The paper investigates the legal status of employment when a PKWT is not legally signed and the realization of workers' rights using a normative juridical method using a statute and case approach.  The findings reveal that the employment connection is regarded valid whenever the worker performs activities under employer supervision, regardless of contract formality.  The court declared the firing unconstitutional and granted compensation of Rp130,000,000.  The study comes to the conclusion that substantive employment elements work, remuneration, and subordination determine the legitimacy of employment relations and that employers cannot use administrative flaws in PKWT to avoid legal obligations